Exploring Pre-Service Teachers’ Argumentation Skills, Socioscientific Issues (Ssi) Related Knowledge And Pedagogical Content Knowledge - Pillai, Rajeswari Vellu (2018)
The objectives of this study were to explore the changes in pre-service teachers’ argumentation skills, socio scientific issue (SSI)-related knowledge and pedagogical content knowledge (PCK) upon progressive exposure to SSI-based projects. This qualitative study was carried out with sixteen pre-service science teachers from a Teacher Training Institute in Malaysia. At the time of study, these students were in the final year of the Bachelor of Teaching Degree Programme. SSI-based projects were implemented as a component of Science Technology and Society course in five topics over a period of one semester. Implementation of SSI-based projects is highly relevant with the context studied as these students will be joining the primary teaching profession after completing this course. As there is strong evidence that pre-service teachers have the power to access multiple number of students across different grades and levels throughout their career, educating these groups of students on SSIs is imperative. Argumentation skills and the knowledge were explored using open-ended tests, interviews and observations. PCK was explored using open-ended tests and interviews. Argumentation skills was analysed using Toulmin’s Argumentation Pattern and Erduran’s five levels of argumentation skills. Thematic analysis was carried out to analyse acquired SSI related knowledge and PCK about SSI-based projects. Triangulation of the findings obtained from all the three measures indicate that the preservice teachers acquired improved argumentation skills and SSI related knowledge progressively after experiencing a series of five projects on SSI. The acquired SSI related knowledge was also in line with the required content knowledge of the STS curriculum.